Cellular therapy in neuromyelitis optica spectrum disorder - Zhong, Kang; Tang, Yulan (Frontiers in Neurology, 2025)
Neuromyelitis optica spectrum disorder (NMOSD) is a debilitating neuroimmune condition characterized by recurrent inflammatory episodes that result in progressive disability, substantial psychological distress, and significant economic burdens. While current immunosuppressive therapies reduce relapse rates, they fail to achieve a definitive cure. Cellular therapy has emerged as a novel therapeutic strategy, offering potential disease modification through immune cell modulation and immune system reorganization via in vivo transplantation of adult stem cells or genetically engineered somatic cells. This review synthesizes recent advancements in cellular therapy for NMOSD, aiming to improve understanding of it in NMOSD disease and provide a roadmap for future research.